PENGELOLAAN DESTINASI WISATA OLEH PEMERINTAH KABUPATEN SOLOK TAHUN 2014-2015 (STUDI OBJEK WISATA DANAU SINGKARAK) - Maiwa, Ildha N.; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to look at how management is done by the Government of Solok Regency Year 2014-2015 in managing the destination attractions Lake Singkarak. The thing that must be owned by the managing namely management. George R. Terry suggests management is a typical process that consists of the actions of planning, organizing, implementing, and monitoring where in each field used both knowledge and expertise that is followed in sequence in order to attempt to achieve the targets that have been set previously. This study uses qualitative research methods with descriptive research, which can be interpreted as a problem-solving process was investigated by describing the state of the research subjects were based on the facts that appear during the study were then followed by the popularity of existing theories. The results showed that the management undertaken by the government in 2014-2015 Solok district in which there are a manajemn that is in the planning process, Solok regency government has not increased significantly and are likely still the same every year. At its organization must put people at the fields under their control that the implementation of tourism development Lake Singkarak done well. In the implementation of tourism development Lake Singkarak there are weaknesses in the management of government where government management Solok district less empowerment of tourism awareness to the public so that the difficulty of getting an agreement with the community in the implementation of which has been planned. The regulatory process in the development of attractions Lake Singkarak conducted by the Government of the District of Solok, Solok regency BPKDS and society. Keywords: Management of County Government Solok, Destinations Attractions Lake Singkarak